Sustainability and Innovation: Incorporating Waste from Ophthalmic Lenses into Natural Rubber Composites - José Afonso Rocha; Carlos Toshiyuki Hiranobe; Dener da Silva Souza; Samara da Silva Araújo; Márcia Ferreira Hiranobe; Guilherme Henrique Barros de Souza; Elmer Mateus Gennaro; Flávio Camargo Cabrera; Guilherme Pina Cardim; Michael Jones da Silva; Erivaldo Antônio da Silva; José Francisco Resende da Silva; et al. (Recycling)
This study investigates the recycling of ophthalmic lens waste (OLW) in the production of vulcanized natural rubber (NR) composites, aiming to promote sustainability and reduce costs. To this end, Vietnamese natural rubber and ophthalmic lens waste were used, varying the filler content from 0 to 50 phr. Rheological tests demonstrated that the addition of OLW decreases the cure time. The crosslink density, assessed through the Flory–Rehner and Mooney–Rivlin methods, exhibited an increase with the incorporation of a reinforcement. Thermal and spectroscopic analyses demonstrated the thermal stability of the composites and the absence of chemical interactions between the polymer matrix and the OLW. Mechanical tests showed that the composites exhibit satisfactory tensile and tear resistance, although the filler primarily acts as a filler rather than a structural reinforcement. Thus, the incorporation of OLW in NR composites emerges as a viable alternative for the reuse of industrial waste, fostering more sustainable and efficient practices in the polymer industry.